Optimization of volume fracturing technology for shallow bow horizontal well in a tight sandstone oil reservoir - Gao, Chaoli; Cheng, Shiqing; Wang, Mingwei; Wu, Wen; Gao, Zhendong; Li, Song; Meng, Xuangang (Frontiers in Energy Research, 2023)
Chang 6 reservoir in Yanchang oilfield is mainly a burial depth of 550~800m. The average porosity of the reservoir is 9.4%, the average permeability is 1.1md, the physical property is poor and the heterogeneity is strong. Multistage fracturing of horizontal wells is easy to form only one large horizontal fracture, and it is difficult to control the fracture height and length. The new mining method of "bow horizontal well + multistage horizontal joint" can effectively increase the multistage horizontal joint's spatial position, which improves the drainage area and stimulation efficiency of oil wells. Due to the reservoir's low permeability and strong heterogeneity, the single well mode of "bow horizontal well + multistage horizontal fracture" cannot effectively produce Chang 6 reservoir. To improve the production degree of the g 6 reservoir, the fracture model is established using equivalent conductivity and the multigrid method. The pressure response functions of horizontal wells and volume fracturing horizontal wells are established by using the source function. The volume fracturing design parameters of the horizontal well are optimized, and the fracturing design parameters of the horizontal section are defined. The simulation results show that the optimal length of a horizontal well is 800m, the optimal fracture interval is 120m/ segment, and the optimal half-length is 90m, which provides a theoretical basis for the efficient development of a shallow tight reservoir.